ANALISIS KEBUTUHAN AIR BERSIH DI KECAMATAN NANGGALO KOTA PADANG - Putri Rahma Safira; Sri Mariya (DEPARTEMEN GEOGRAFI FIS UNP, 2021)
The purpose of this research is (1) determine the prediction of the population in Nanggalo District in 2019-2028; (2) knowing the prediction of water demand in Nanggalo District in 2019-2028. This type of research is descriptive quantitative. The data analysis method is a geometric method by calculating the prediction of the population and the method of analyzing the need for clean water to calculate the predicted clean water needs of Nanggalo District in 2019-2027. Based on the results of the study, it shows that: (1) The prediction results of the population in Nanggalo District in 2019 are 62,049 people. Meanwhile in 2028 the predicted population of Nanggalo District will be 67,129 people; (2) The prediction result of clean water demand in Nanggalo District in 2019 is 71.09 liters / second. Meanwhile, in 2028 the prediction of clean water demand in Nanggalo District is 76.85 liters / second, where the current clean water capacity is 68.47 literst /second so that it is not sufficient for water needs in 2028